ANALISIS DAMPAK LINGKUNGAN DALAM KEBIJAKAN PERLINDUNGAN SITUS RATU BOKO MENUJU PENGEMBANGAN PARIWISATA YANG BERKELANJUTAN - Nugraha, Bima Setya; Putri, Lana Prihanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2016)
Daerah Istimewa Yogyakarta known to have many tourist destinations in the form of heritage for example Ratu Boko site. The site Ratu Boko is a historic relic that was built around the 8th century during the reign of Rakai Panangkaran, one of the descendants Wangsa Syailendra. The development of these tourist destinations are increasingly dynamic. The development of tourism activities in sites of historical and cultural heritage of course have an impact on the environment around the site. This study used qualitative descriptive methods, using data derived from primary data source (observations and interviews) and secondary data sources (study of literature). This papers restrain only on based descriptive analysis from data and not using statistic to analysis. The results of this research found that there are positive and negative impacts arising from the development of this tourist destination. Keywords: tourism destination, the site Ratu Boko, impact, qualitative